Workation Phenomenon and Hotel Selection for Hotel Room Design Considerations - Fitriani, Anindita Dara; Maharani, Yuni (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
This study explores the factors influencing hotel selection for workation. The term workation, derived from the combination of the words